How effective is mammography in detecting breast cancer recurrence in women after Breast Conservation Therapy (BCT) – A systematic literature review. Issue 3 (August 2016) - Curran, J.
Abstract: Breast Conservation Therapy (BCT) is now seen as the treatment of choice for early-stage breast cancer, leading to a rising demand for post-operative surveillance. Ongoing mammographic surveillance of the post-operative breast is necessary to minimise the morbidity risk from recurrence. This review evaluates the diagnostic value of mammography following BCT, and identifies the possible challenges with mammography regarding imaging, interpretation and test performance when investigating the treated breast. Relevant literature was reviewed and critically analysed. Three studies reported that surveillance mammography provided a significant survival advantage through early detection of recurrence. Five studies recognised the diagnostic challenges of surveillance mammography following BCT, reporting reduced sensitivity after breast surgery. The need for a more tailored screening strategy after treatment for breast cancer was highlighted in four studies. Although overall mammographic sensitivity is reduced after BCT, it is still proven to be effective in detecting recurrences, therefore remains an important surveillance tool. Highlights: Mammographic surveillance – survival advantage. Sensitivity reduced post-surgery. Tailored strategy needed.